The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/2317-4889201720170114
|View full text |Cite
|
Sign up to set email alerts
|

Gold, iron and manganese in central Amapá, Brazil

Abstract: ABSTRACT:Greenstone belts with deposits of gold, iron and manganese are common in the Paleoproterozoic Maroni-Itacaiunas Tectonic Province of the Guiana Shield. In Brazil, in the State of Amapá and northwest of Pará, they are represented by the Vila Nova Group, constituted by a basal unit of metabasalts, covered by metasediments of clastic and chemical origin. The basal metasediments, the Serra do Navio Formation, are made of a cyclothem with lenses of manganese marbles at the top of each cycle. Under the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 8 publications
(10 reference statements)
2
21
0
Order By: Relevance
“…We revise the published information, updating it with observations recently made in the field by one of the authors. We show that exposures at new mining excavations and aero-geophysical information demonstrate that the mafic-ultramafic complex is intrusive in the Vila Nova Group, similarly to what we saw at the area of the Serra da Canga (Scarpelli & Horikava 2017), and that the auriferous quartzite-conglomerate unit of the area occurs at the top, and not at the base, of the column of metasediments, actually overlaying the Vila Nova Group. Examining the Água Boa auriferous deposit, we saw a very good degree of similarity between the principal structural control of the gold mineralization of this deposit with that of the Tucano Mine, practically outlining a pattern worth to follow in general exploration for gold in the MIP.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…We revise the published information, updating it with observations recently made in the field by one of the authors. We show that exposures at new mining excavations and aero-geophysical information demonstrate that the mafic-ultramafic complex is intrusive in the Vila Nova Group, similarly to what we saw at the area of the Serra da Canga (Scarpelli & Horikava 2017), and that the auriferous quartzite-conglomerate unit of the area occurs at the top, and not at the base, of the column of metasediments, actually overlaying the Vila Nova Group. Examining the Água Boa auriferous deposit, we saw a very good degree of similarity between the principal structural control of the gold mineralization of this deposit with that of the Tucano Mine, practically outlining a pattern worth to follow in general exploration for gold in the MIP.…”
Section: Introductionsupporting
confidence: 75%
“…A detailed petrographic study of the Amapari Greenstone belt at Serra do Navio has shown that it was subject twice to regional metamorphism, with an intermediate episode of thermal metamorphism caused by syntectonic granitic intrusions. Local fold axis and elongation of greenstone to north and northeast suggest that these structures might be remnants of the first regional metamorphism (Scarpelli & Horikava 2017).…”
Section: General Geologymentioning
confidence: 99%
See 3 more Smart Citations